184 Urotensin ii induces cardiomyocytes hypertrophy via activation of the mapk and camkii signalling pathways. (5th June 2017) - Ali, Hadeel Al; Lambert, David; Rodrigo, Glenn
Abstract : Introduction: The normal concentration of circulating Urotensin II (UII) is elevated in heart failure (Ng et al. 2002). UII has been shown to be involved the development of pathological cardiac hypertrophy (Tzanidis et al. 2003). The aim of this study is to investigate the cellular mechanism by which UII results in ventricular hypertrophy. Methodology: Adult Rat Ventricular Myocytes (ARVMs) were isolated from male Wistar rats by enzymatic digestion and placed into primary culture. ARVMs were cultured in six wells plate for up 48 hours. To induce hypertrophy, cells were treated with UII (200 nM) or phenylephrine (10 µM), and hypertrophy quantified as Length/Width (L/W) ratio from photomicrographs. Results Cultured AVRMs exposed to either phenylephrine or UII developed hypertrophy in a time-dependent manner, with a significant reduction in L/W ratio after incubation with UII for 24 hours in comparison with control group (4.25±0.06, n=362 vs. 4.45±0.06, n=335) (p<0.05) or 48 hours (3.99±0.06, n=209 vs. 4.53±0.10, n=126) (p<0.0001).Treatment of AVRMs with phenylephrine induced a similar level of hypertrophy to that seen by UII, to alteration in the morphology of myocytes, there was a significant reduction in L/W ratio after incubation with phenylephrine for 24 hours in comparison with control group (4.08±0.05, n=338 vs. 4.45±0.06, n=335) (p<0.05) or 48 hours (3.77±0.08, n=141 vs. 4.53±0.10, n=126) (p<0.0001). To study the role of ERK1/2, P38 and CaMKII signalling in the UII-induced hypertrophy, cultured ARVMs were treated with either 5µM of ERK1/2 inhibitor (PD 184352), 10 µM of P38 inhibitor (SB 202190) or 5 µM CaMKII (KN-93) for 30 min prior to stimulation with UII (200 nM). Inhibition of all three signalling pathways completely blocked the UII-induced hypertrophy after 48 hours; from (3.87±0.05, n=420) in UII group to (4.64±0.08, n=195) (UII + PD) (p<0.0001) and from (3.87±0.05, n=420) in UII group to (4.86±0.09, n=212) (UII + SB) (p<0.0001). Inhibition of CaMKII from (3.39±0.04, n=386) in UII group to (4.14±0.06, n=223) (UII + CaMKII) (p<0.0001). Conclusion: These data show that the ERK1/2, p38 and CaMKII signalling pathways are involved in the hypertrophic response to UII. I am currently using Western Blot to confirm the involvement of ERK1/2, P38 and CaMKII pathways. References: 1Ng LL, Loke I, O'Brien RJ, Squire IB, Davies JE. Circulation 2001;106(23):2877–2880. 2Tzanidis A, Hannan RD, Thomas WG, Onan D, Autelitano DJ, See F, Kelly DJ, Gilbert RE, Krum H. Circulation Research: Journal of the American Heart Association, 203;93(3):246–253.